Study On Low-Cycle Fatigue Behavior Of Cast Hybrid Metal Matrix Composites - Iqbal, AKM Asif (Universiti Malaysia Pahang, 2015)
The low-cycle fatigue (LCF) behavior, especially the fracture initiation mechanism in a cast hybrid metal matrix composite (MMC), was studied experimentally and numerically. The conventional three-point bending fatigue test was carried out and fractographic analysis was conducted to observe the fracture initiation site. Experimental results showed that microcracks in the LCF initiated at the particle–matrix interface which was located in the hybrid clustering region. Due to continued fatigue cycling, interface debonding occurred, created additional secondary microcracks and the microcrack coalesced with other nearby microcracks. As far as the numerical study is concerned, three-dimensional (3-D) unit-cell models of the hybrid MMC consisting of reinforcement clustering and non-clustering regions were developed by using the finite element method. The stress–strain distributions in both the reinforcement clustering and non-clustering regions were analyzed. The numerical results confirmed that the stress concentration occurred on the reinforcement–matrix interface located in the clustering region and provided reasonable agreement with the experimental observations.